Adaptation behaviour of vegetable growers in crisis situations - Boban Paul (Department of Agricultural Extension, College of Horticulture, 2002)
Kerala, the green stretch, in the south west cost of India, is delineated from other states by Western Ghats stretching around six hundred kilometers of its Eastern boundary. These hill ranges creates an exclusive climatic conditions in this land. The soil and whether factors have lead to diversity of plant population and also the crops cultivated here. Like other states of India, the crop loss and consequent economic crises occur in Kerala farming also. However the root causes of the crises are different here compared to other states. There it happens as a results of flood, droughts and storms where in Kerala the economic loss results mainly from pest and disease incidence, land slides etc. Kerala is well known for the production of spices and plantation crops. In last two or three decades the commercial cultivation of vegetables also was started in the state. Still a major portion of state's requirement of vegetables are met by products from neighbouring states. The government through its Department of Agriculture and the Vegetable and Fruits Promotion Council of Kerala are trying to increase vegetable production in the state. It was in this context, the present study was undertaken with the objectives such as identifying the different crisis situations encountered by commercial vegetable growers, identifying the methods of adaptation in these crisis situations, rationality behind those methods of adaptation and finally the perception of commercial vegetable growers about the external intervention of developmental agencies in crisis situation. The study was conducted in Ernakulam district which was a traditional vegetable growing area. More over the activities of Department of Agriculture and vegetable and fruits promotion council of Kerala was in progress for the promotion of vegetable production. A two stage sampling technique was used to select three panchayats for the selection of respondents. From the selected panchayat fifty vegetable growers each were randomly identified and they formed the respondents.